2010
DOI: 10.1523/jneurosci.0661-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoffs and Constraints on Neural Representation in Networks of Cortical Neurons

Abstract: Neural representation is pivotal in neuroscience. Yet, the large number and variance of underlying determinants make it difficult to distinguish general physiologic constraints on representation. Here we offer a general approach to the issue, enabling a systematic and well controlled experimental analysis of constraints and tradeoffs, imposed by the physiology of neuronal populations, on plausible representation schemes. Using in vitro networks of rat cortical neurons as a model system, we compared the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 53 publications
7
41
0
3
Order By: Relevance
“…The finding that stimulus responses stabilized, probably means that subsequent presentation of the cue reactivated the trace and did not interfere with the established activity-connectivity equilibrium. Marom and coworkers showed that repeated stimulation of cultured cortical networks induced site-specific responses that enabled deduction of the stimulation site during up to 24 h (Shahaf et al 2008;Kermany et al 2010). This further supports the view that presentation of the original cue reactivates the trace.…”
Section: Discussionmentioning
confidence: 69%
“…The finding that stimulus responses stabilized, probably means that subsequent presentation of the cue reactivated the trace and did not interfere with the established activity-connectivity equilibrium. Marom and coworkers showed that repeated stimulation of cultured cortical networks induced site-specific responses that enabled deduction of the stimulation site during up to 24 h (Shahaf et al 2008;Kermany et al 2010). This further supports the view that presentation of the original cue reactivates the trace.…”
Section: Discussionmentioning
confidence: 69%
“…The late component is sensitive to glutamate receptor blockers, supporting a polysynaptic origin (Jimbo et al 2000). It is this component that reflects how a local stimulus will eventually invade the network, and that thus should have predictable dynamics (Kermany et al 2010). Understanding what influences the properties of the polysynaptic response is therefore crucial for a defined interaction with neuronal networks.…”
Section: Fig 2 Network Burst Interval and Length Statisticsmentioning
confidence: 96%
“…Π’ соврСмСнных Ρ€Π°Π±ΠΎΡ‚Π°Ρ… ΠΏΠΎ ΠΈΠ·ΡƒΡ‡Π΅Π½ΠΈΡŽ элСктрофизиологичСской активности Π½Π΅ΠΉΡ€ΠΎΠ½Π°Π»ΡŒΠ½Ρ‹Ρ… ΠΊΡƒΠ»ΡŒΡ‚ΡƒΡ€ in vitro особоС Π²Π½ΠΈΠΌΠ°Π½ΠΈΠ΅ удСляСтся Ρ„Π΅Π½ΠΎΠΌΠ΅Π½Ρƒ спонтанной ΠΏΠ°Ρ‡Π΅Ρ‡Π½ΠΎΠΉ активности [1][2][3][4][5][6][7][8][9][10]. ΠŸΠΎΠΏΡƒΠ»ΡΡ†ΠΈΠΎΠ½Π½ΠΎΠΉ ΠΏΠ°Ρ‡ΠΊΠΎΠΉ (ΠΈΠ»ΠΈ просто ΠΏΠ°Ρ‡ΠΊΠΎΠΉ) активности ΠΊΡƒΠ»ΡŒΡ‚ΡƒΡ€Ρ‹ называСтся явлСниС Ρ€Π΅Π·ΠΊΠΎΠ³ΠΎ возрастания активности Π³Ρ€ΡƒΠΏΠΏ Π½Π΅ΠΉΡ€ΠΎΠ½ΠΎΠ² Π² Ρ‚Π΅Ρ‡Π΅Π½ΠΈΠ΅ ΠΊΠΎΡ€ΠΎΡ‚ΠΊΠΎΠ³ΠΎ ΠΏΡ€ΠΎΠΌΠ΅ΠΆΡƒΡ‚ΠΊΠ° Π²Ρ€Π΅ΠΌΠ΅Π½ΠΈ.…”
Section: Introductionunclassified
“…Π’ Ρ€Π°Π±ΠΎΡ‚Π΅ [5] исслСдуСтся Π²Ρ€Π΅ΠΌΠ΅Π½Π½ΠΎΠΉ порядок вовлСчСния Π½Π΅ΠΉΡ€ΠΎΠ½ΠΎΠ² Π² Π²Ρ‹Π·Π²Π°Π½Π½ΡƒΡŽ элСктричСской стимуляциСй ΠΏΠ°Ρ‡ΠΊΡƒ активности. Авторы Ρ€Π°Π±ΠΎΡ‚Ρ‹ [6] ΡΡ€Π°Π²Π½ΠΈΠ²Π°ΡŽΡ‚ нСсколько ΠΌΠ΅Ρ‚ΠΎΠ΄ΠΎΠ² Π°Π½Π°Π»ΠΈΠ·Π° активности сСтСй Π½Π΅ΠΉΡ€ΠΎΠ½ΠΎΠ², основанных Π»ΠΈΠ±ΠΎ Π½Π° частотной характСристикС ΠΎΡ‚Π²Π΅Ρ‚Π° Π½Π΅ΠΉΡ€ΠΎΠ½ΠΎΠ² Π½Π° стимулы (Π½Π°ΠΏΡ€ΠΈΠΌΠ΅Ρ€, ΠΎΠ±Ρ‰Π΅Π΅ количСство Π°ΠΊΡ‚ΠΈΠ²Π°Ρ†ΠΈΠΉ Π½Π΅ΠΉΡ€ΠΎΠ½Π° Π² Ρ‚Π΅Ρ‡Π΅Π½ΠΈΠ΅ Π½Π΅ΠΊΠΎΡ‚ΠΎΡ€ΠΎΠ³ΠΎ Π²Ρ€Π΅ΠΌΠ΅Π½ΠΈ послС стимула), ΠΏΡ€ΠΈ этом тСряСтся Π²Ρ€Π΅ΠΌΠ΅Π½Π½ΠΎΠΉ порядок Π°ΠΊΡ‚ΠΈΠ²Π°Ρ†ΠΈΠΈ Ρ€Π°Π·Π»ΠΈΡ‡Π½Ρ‹Ρ… Π½Π΅ΠΉΡ€ΠΎΠ½ΠΎΠ², Π»ΠΈΠ±ΠΎ Π½Π° ΡƒΡ‡Π΅Ρ‚Π΅ Π²Ρ€Π΅ΠΌΠ΅Π½ΠΈ ΠΏΠ΅Ρ€Π²ΠΎΠΉ Π°ΠΊΡ‚ΠΈΠ²Π°Ρ†ΠΈΠΈ ΠΊΠ°ΠΆΠ΄ΠΎΠ³ΠΎ ΠΈΠ· рассматриваСмых Π½Π΅ΠΉΡ€ΠΎΠ½ΠΎΠ². Для ΠΊΠ°ΠΆΠ΄ΠΎΠ³ΠΎ ΠΈΠ· ΠΌΠ΅Ρ‚ΠΎΠ΄ΠΎΠ² Π°Π½Π°Π»ΠΈΠ·Π° обсуТдаСтся Π΅Π³ΠΎ Π½Π°ΠΈΠ»ΡƒΡ‡ΡˆΠ°Ρ ΠΎΠ±Π»Π°ΡΡ‚ΡŒ примСнСния.…”
Section: Introductionunclassified